ĐẶNG HUY TRỨ ‘S THOUGHT OF SELF-RELIANCE AND AUTONOMY AND ITS HISTORICAL MEANING - Long, Cao Xuân (International Journal of Psychosocial Rehabilitation, 2020)
Dang Huy Tru (At Dau 1825 - Giap Tuat 1874) is not only a writer, poet, economist, and politician but also one of the first thinkers of "germination of civilization in Vietnam"; His ideas in many fields are quite rich and distinctive, and self-reliance and autonomy are among the core thoughts . Due to some subjective and objective conditions, such ideas have not become a reality in Viet Nam. However, if the limitations of historical conditions are filtered out, his ideas may be useful historical lessons for the current reform of the country.